My father's shadow : intergenerational conflict in African American men's autobiography - Dudley, David L. (University of Pennsylvania Press, 1991)
David L. Dudley explores African American men's autobiographies, starting with Frederick Douglas and moving on through Booker T. Washington, W.E.B. Du Bois, Richard Wright, James Baldwin, Eldridge Cleaver, and Malcolm X.